2011
DOI: 10.1007/s12223-011-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in proteolytic activity and gene profiles of fungal strains isolated from the total parenteral nutrition patients

Abstract: Fungal infections constitute a serious clinical problem in the group of patients receiving total parenteral nutrition. The majority of species isolated from infections of the total parenteral nutrition patients belong to Candida genus. The most important factors of Candida spp. virulence are the phenomenon of “phenotypic switching,” adhesins, dimorphism of fungal cells and the secretion of hydrolytic enzymes such as proteinases and lipases, including aspartyl proteinases. We determined the proteolytic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…In C. albicans , SAPs known as sap protein family (Sap 1–10) are involved in the maintenance of cell wall integrity and regulation of attachment of C. albicans with human epithelial cells and neutrophils ( Buu and Chen, 2013 ). Other than C. albicans , some NAC species including C. dubliniensis, C. tropicalis, C. parapsilosis , and C. glabrata are also capable of producing SAPs ( Naglik et al, 2003 ; Sikora et al, 2011 ). In this study, qualitative measurement of SAPs production in all the tested strains revealed the intense reduction upon treatment with QA-UDA combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. albicans , SAPs known as sap protein family (Sap 1–10) are involved in the maintenance of cell wall integrity and regulation of attachment of C. albicans with human epithelial cells and neutrophils ( Buu and Chen, 2013 ). Other than C. albicans , some NAC species including C. dubliniensis, C. tropicalis, C. parapsilosis , and C. glabrata are also capable of producing SAPs ( Naglik et al, 2003 ; Sikora et al, 2011 ). In this study, qualitative measurement of SAPs production in all the tested strains revealed the intense reduction upon treatment with QA-UDA combinations.…”
Section: Discussionmentioning
confidence: 99%
“…SAPs have been recognized as one of the virulence factors of Candida spp. particularly, in C. albicans , ten aspartyl proteinases (Sap1–Sap10) facilitate the active penetration into the host cells ( Smolenski et al, 1997 ; Sikora et al, 2011 ). Among the 10 Saps, Sap1–Sap8 secretes and diffuses into surrounding medium, while Sap9 and Sap10 attaches to the cell surface ( Mayer et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most C. glabrata strains (71%) tested positive for all three analysed genes – genotype YPS2 + YPS4 + YPS6 . The results of this study confirm the previously undertaken ones on the prevalence of those genes in C. glabrata strains isolated from patients under long‐term total parenteral nutrition . Most of the analysed C. nivariensis strains did not present any of the tested genes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study confirm the previously undertaken ones on the prevalence of those genes in C. glabrata strains isolated from patients under long-term total parenteral nutrition. 28 Most of the analysed C. nivariensis strains did not present any of the tested genes. This could indicate a lower virulence potential than in C. glabrata.…”
Section: (A) (B) (C)mentioning
confidence: 95%
“…In C. albicans, ten genes encoding for lipases have been identified and it has been shown that mutants were significantly less virulent in a murine intravenous infection model. Sequences similar to C. albicans (LIP1-10) were also detected in C. tropicalis, but not in C. glabrata [78][79][80][81][82].…”
Section: Enzyme Productionmentioning
confidence: 99%